Metagenomic analysis of soil microbial communities - Đokić Lidija; Savić M.; Narančić Tanja; Vasiljević Branka (Archives of Biological Sciences, 2010)
Ramonda serbica and Ramonda nathaliae, rare resurrection plants growing in the Balkan Peninsula, produce a high amount of phenolic compounds as a response to stress. The composition and size of bacterial communities in two rhizosphere soil samples of these plants were analyzed using a metagenomic approach. Fluorescent in situ hybridization (FISH) experiments together with DAPI staining showed that the metabolically active bacteria represent only a small fraction, approximately 5%, of total soil bacteria. Using universal bacteria - specific primers 16S rDNA genes were amplified directly from metagenomic DNAs and two libraries were constructed. The Restriction Fragment Length Polymorphism (RLFP) method was used in library screening. Amongst 192 clones, 35 unique operational taxonomic units (OTUs) were determined from the rhizosphere of R. nathaliae, and 13 OTUs out of 80 clones in total from the library of R. serbica. Representative clones from each OTU were sequenced. The majority of sequences from metagenomes showed very little similarity to any cultured bacteria. In conclusion, the bacterial communities in the studied soil samples showed quite poor diversity. .